Elimination of plasmid-linked polyglutamate production by Bacillus subtilis (natto) with acridine orange. - Hara, T (1982)
Treatment of Bacillus subtilis (natto) strains Asahikawa, F, and M with acridine orange resulted in the conversion of approximately 64.2% of the Asahikawa population, 22.4% of the F population, and 9.2% of the M population to polyglutamate-nonproducing colonies. Such curing is suggestive of the involvement of plasmid DNA. Samples of cleared lysates of both parental and their cured strains were subjected to agarose gel electrophoresis to determine the plasmid composition. Parental strains were found to possess a plasmid, but polyglutamate-nonproducing derivatives were missing the plasmid. The plasmid-linked polyglutamate production, which was originally isolated from B. subtilis (natto), could be transformed in B. subtilis.